Mode of Action Assignment of Chemicals Using Toxicogenomics: A Case Study with Oxidative Uncouplers - Hawliczek-Ignarski, Alessa; Cenijn, Peter; Legler, Juliette; Segner, Helmut; Legradi, Jessica (Frontiers in Environmental Science, 2017)
A criterion frequently used to group chemicals in risk assessment is “mode of toxic action” (MoA). Routinely, structure-based approaches are used for the MoA categorization of chemicals, but they can produce conflicting results or fail to classify compounds. Biological activity-based approaches such as toxicogenomics which provide an unbiased overview of the transcriptomic changes after exposure to a compound may complement structure-based approaches in MoA assignment. Here, we investigate whether toxicogenomic profiles as generated after in vitro exposure of an established cell line (C3A hepatoma cells) are able to group together chemicals with an uncoupling MoA, and to distinguish the uncouplers from chemicals with other MoAs. In a first step, we examined whether chemicals sharing the same uncoupling of oxidative phosphorylation (OXPHOS) MoA produce similar toxicogenomic profiles and can be grouped together. In a next step, we tested whether the toxicogenomic profiles discriminate between OXPHOS and chemicals displaying a (polar) narcotic MoA. Experimentally, cells were exposed in vitro to equipotent concentrations of the test compounds and gene expression profiles were measured. The resulting toxicogenomic profiles assigned OXPHOS to one cluster and discriminated between the OXPHOS and the (polar) narcotics. In addition, the toxicogenomics data revealed that one and the same chemical can display multiple MoAs, which may help to explain conflicting results of MoA classification from structure-based approaches. The results strongly suggest the feasibility of MoA grouping of chemicals by using in vitro cell assay-based toxicogenomic profiles.